Fibrinogen is a promising biomarker for chronic obstructive pulmonary disease: evidence from a meta-analysis. Issue 7 (24th July 2020) - Zhou, Bo; Liu, Shufang; He, Danni; Wang, Kundi; Wang, Yunfeng; Yang, Ting; Zhang, Qi; Zhang, Zhixin; Niu, Wenquan
Abstract: Backgrounds: Some studies have reported association of circulating fibrinogen with the risk of chronic obstructive pulmonary disease (COPD), and the results are conflicting. To yield more information, we aimed to test the hypothesis that circulating fibrinogen is a promising biomarker for COPD by a meta-analysis. Methods: Data extraction and quality assessment were independently completed by two authors. Effect-size estimates are expressed as weighted mean difference (WMD) with 95% confidence interval (95% CI). Results: Forty-five articles involving 5586/18604 COPD patients/controls were incorporated. Overall analyses revealed significantly higher concentrations of circulating fibrinogen in COPD patients than in controls (WMD: 84.67 mg/dl; 95% CI: 64.24–105.10). Subgroup analyses by COPD course showed that the degree of increased circulating fibrinogen in patients with acute exacerbations of COPD (AECOPD) relative to controls (WMD: 182.59 mg/dl; 95% CI: 115.93–249.25) tripled when compared in patients with stable COPD (WMD: 56.12 mg/dl; 95% CI: 34.56–77.67). By COPD severity, there was a graded increase in fibrinogen with the increased severity of COPD relative to controls (Global Initiative for Obstructive Lung Disease (GOLD) I, II, III, and IV: WMD: 13.91, 29.19, 56.81, and 197.42 mg/dl; 95% CI: 7.70–20.11, 17.43–40.94, 39.20–74.41, and −7.88 to 402.73, respectively). There was a low probability of publication bias. Conclusion: Our findings indicate a graded, concentration-dependent, significant relation between higher circulating fibrinogen and more severity of COPD.